2021
DOI: 10.1111/1346-8138.15952
|View full text |Cite
|
Sign up to set email alerts
|

BP230 IgE autoantibodies in topical‐steroid‐resistant bullous pemphigoid

Abstract: Bullous pemphigoid is an autoimmune disease characterized by pruritic urticarial erythema and tense blisters, affecting mainly elderly people. Histopathology reveals subepidermal blisters with eosinophilic infiltration, and direct immunofluorescence (IF) demonstrates deposits of IgG and/or C3 to the basement membrane zone (BMZ). 1 Autoantibodies in BP sera were against hemidesmosomal proteins BP180 and BP230, which are involved in anchoring basal keratinocytes in the epidermis to the dermis. 2 In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It has also been reported that the level of anti-BP230 IgE is associated with disease activity or local eosinophil infiltration ( 125 , 126 ). Moreover, anti-BP230 IgE is more common in patients resistant to topical corticosteroids, suggesting that it can be used as a marker for systemic corticosteroid therapy ( 127 ). In addition, in vitro experiments have shown that anti-BP180 IgE can cause a decline in keratinocyte adhesion and hemidesmosomal density ( 128 ), suggesting its function in blister formation.…”
Section: Type 2 Inflammation In Bp and Potential Therapeutic Targetsmentioning
confidence: 99%
“…It has also been reported that the level of anti-BP230 IgE is associated with disease activity or local eosinophil infiltration ( 125 , 126 ). Moreover, anti-BP230 IgE is more common in patients resistant to topical corticosteroids, suggesting that it can be used as a marker for systemic corticosteroid therapy ( 127 ). In addition, in vitro experiments have shown that anti-BP180 IgE can cause a decline in keratinocyte adhesion and hemidesmosomal density ( 128 ), suggesting its function in blister formation.…”
Section: Type 2 Inflammation In Bp and Potential Therapeutic Targetsmentioning
confidence: 99%
“…BP180 IgE was detected in 22%–100% of BP patients ( 34 , 35 ). BP230-specific IgE is prevalent in BP ( 35 , 36 ). The high IgE autoantibody level in BP patients may necessitate aggressive treatment ( 37 ).…”
Section: Immune Cellsmentioning
confidence: 99%
“…Other studies have detected anti-BP230 IgE in patients with BP [ 111 , 112 ] and their levels have been associated with disease activity and local eosinophil infiltration [ 113 , 114 ]. Additionally, anti-BP230 IgE is more common among patients who are resistant to topical corticosteroids, being a potential marker for systemic corticosteroid therapy [ 115 ].…”
Section: Therapymentioning
confidence: 99%